The Effects of Tax Avoidance and Gender Diversity on Firm Value - Harsono, Budi; Wati, Erna; Anita; Tang, Sukiantono (Global Financial Accounting Journal, 2024)
This study intended to inspect the correlation of tax avoidance and gender diversity to firm value listed in Indonesia Stock Exchange (ISE). This survey used firm value as dependent variable. Tax avoidance and gender diversity as independent variable. This survey also used control variable such as return on asset, return on equity, firm size, leverage, growth, firm’s industry and firm’s auditor. The sample data of this study used secondary data. Companies listed in Indonesia Stock Exchange (ISE) from year 2015-2019 are the samples of this study. Research conducted data testing using SPSS version 25 and E-Views version 10 application. With total data 2,169 from 2,210, the sample selected based on purposive sampling method. Several tests were carried out in analysing, including descriptive statistics, multicollinearity test, outliers, Hausman, F test, T test, and determination coefficient test. Result shown that both independent variable tax avoidance and gender diversity has no significant effect to influence dependent variable firm value. For control variable only firm size and leverage has significant effect to influence.